The Case for Authentic Assessment - Grant Wiggins (Practical Assessment, Research, and Evaluation, 1990)
Accessed 298,989 times on https://pareonline.net from November 13, 1999 to December 31, 2019. For downloads from January 1, 2020 forward, please click on the PlumX Metrics link to the right.
Keywords: Comparative Testing; Cost Effectiveness; *Educational Assessment; Elementary Secondary Education; Nontraditional Education; Public Opinion; Standardized Tests; *Test Use; Test Validity